2013
DOI: 10.1063/1.4807722
|View full text |Cite
|
Sign up to set email alerts
|

High trapped field performances in thin-wall YBa2Cu3O7−δ bulk cryomagnets

Abstract: Thin-wall YBa2Cu3O7−δ bulk single domains were grown from drilled preforms with a holes network in the aim of increasing the specific areas and diminishing the oxygen diffusion paths. By applying a progressive annealing at high temperature under oxygen pressure (10 MPa), crack-free superconductors were obtained in a very short time (less than 3 days). A crack-free microstructure fostered large size persistent current loops, which boosted the trapped field performances. A trapped field Bmax = 5.2 T at 17 K was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Akin to YBa 2 Cu 3 O 7‐δ (YBCO) and (Rare‐Earth)Ba 2 Cu 3 O 7 (REBCO) cryomagnets, 8,9 bulk MgB 2 could be used for various applications such as the delivery of drug at specified locations in the human body using an external magnetic force, 10 magnetic separation systems, 11 portable nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) devices, 12 generators or motors 13,14 etc… For all these applications, the trapped magnetic field of present MgB 2 bulks must be improved. According to the Bean model, the trapped field is proportional to the critical current density, J c , and depends on the size of the persistent current loops, 15 that is linked to the sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Akin to YBa 2 Cu 3 O 7‐δ (YBCO) and (Rare‐Earth)Ba 2 Cu 3 O 7 (REBCO) cryomagnets, 8,9 bulk MgB 2 could be used for various applications such as the delivery of drug at specified locations in the human body using an external magnetic force, 10 magnetic separation systems, 11 portable nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) devices, 12 generators or motors 13,14 etc… For all these applications, the trapped magnetic field of present MgB 2 bulks must be improved. According to the Bean model, the trapped field is proportional to the critical current density, J c , and depends on the size of the persistent current loops, 15 that is linked to the sample size.…”
Section: Introductionmentioning
confidence: 99%
“…The second is to enhance the heat dissipation of the solid phase rapidly and effectively to reduce the energy accumulation. Chaud et al reported that a successful YBCO bulk superconductor from drilled preforms with a porous network structure of holes presented a high performance in terms of increasing the specific surface area [15]. As indicated, such a porous structure can increase the surface area ratio, which allows the interfacial energy to be released efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The YBa 2 Cu 3 O 7À (YBCO or Y123) high-temperature superconductor has attracted a significant amount of attention since it was discovered in 1987 (Campbell & Cardwell, 1997;Werfel et al, 2012;Krabbes et al, 2006). Single crystals with a large size and high quality are extremely important for device applications (Bean, 1962;Ren et al, 1993;Morita et al, 1998;Fuchs et al, 2000;Tomita & Murakami, 2003;Babu et al, 2005;Treimer et al, 2012;Kenfaui et al, 2013Kenfaui et al, , 2015Grissonnanche et al, 2014) and fundamental studies (Krabbes et al, 2006;Headings et al, 2011). Of all the methods for growing YBCO single crystals, the self-flux technique (Krauns et al, 1994) is popularly used for producing small crystals.…”
Section: Introductionmentioning
confidence: 99%